Isolation, identification and bioactivity evaluation of mangiferin and genkwanin 5-O-β-primeveroside in gaharu plant parts and finished products for Gaharu Technologies Sdn Bhd - Ngui, William Tet Shung (2019)
Agarwood, produced from the trees of Aquilaria species, has been highly valued since ancient times for its commercial uses as well as medicinal properties such as antidiabetic, constipation and headache. HOGA Gaharu Tea products produced by Gaharu Technologies Sdn Bhd (GTSB) were claimed to be able to help reduce blood sugar levels and constipation. However, traditional recipes are generally not formulated based on scientific data, while beneficial claims are often not substantiated scientifically. Based on recent literature reviews, it has been found that the major phytochemicals responsible for the reported antidiabetic and laxative effects of Aquilaria sinensis are due to mangiferin (1) and genkwanin 5-O-β-primeveroside (4), respectively (Hara et al., 2008; Ito et al., 2012). In the present study, both mangiferin (1) and genkwanin 5-O-β-primeveroside (4) have been successfully isolated from the acetone and MeOH extracts of gaharu leaf material, along with naringenin (2) and iriflophenone 2-O-α-rhamnoside (3). Through MTT assay, safe concentration ranges (above IC50) were determined for all test samples to be subjected to gluconeogenesis assay. Glucose concentration values (µM) are normalised by amount of protein (µg) present in each well as determined from the Bradford Protein assay. It has been shown that mangiferin in various concentrations showed significant glucose suppression effect, while genkwanin 5-O-β-primeveroside was practically ineffective. Normalised gluconeogenesis assay has shown that leaf water extract, with the highest amount of mangiferin (6.00% w/w), exhibited the best glucose production-suppression activity (0.00035 M/g) relative to control (0.00254 M/g). This is followed by twig (0.00090 M/g) which contain 0.50% w/w of mangiferin. Bark (0.00223 M/g) and young shoot (0.00215 M/g) showed no significant glucose suppression activity compared to control, which correlated to the fact that mangiferin was undetectable in these two plant parts. As for the tea products, both Gaharu Tea and Gaharu Cool Tea showed comparable normalised glucose concentration values (0.00172 and 0.00183 M/g, respectively), which correlated to the comparable amounts of mangiferin detected in Gaharu Tea (1.33% w/w) and Gaharu Cool Tea (1.66% w/w). Only 0.18% w/w of mangiferin was detected in GOGA Drink Powder, which corresponded well with the high normalised glucose concentration (0.00221 M/g) determined. Through HPLC quantitative analysis, the amounts of genkwanin 5-O-β-primeveroside were also determined, i.e., leaf 0.55%, Gaharu Tea 0.15%, and Gaharu Cool Tea 0.11%. Genkwanin 5-O-β-primeveroside was undetectable in twig, bark, young shoot, and GOGA Drink Powder. However, no significant gluconeogenesis assay results are associated with genkwanin 5-O-β-primeveroside. From the product consumption perspective, each sachet of Gaharu Tea and Gaharu Cool Tea has comparable amount of mangiferin per serving (approximately 4.10 mg and 5.70 mg, respectively), whereas a bottle of GOGA Drink (300 ml/bottle, which is prepared by dissolving GOGA Drink Powder in water) has lesser amount of mangiferin per serving (0.36 mg). Therefore, it is speculated that consuming Gaharu Tea and Gaharu Cool Tea would result in better glucose suppression activity compared to GOGA Drink per serving.